2008
DOI: 10.1002/path.2489
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of metallothionein predicts chemoresistance in breast cancer

Abstract: Metallothionein (MT) plays a role in fundamental cellular processes such as proliferation, apoptosis and differentiation. We examined MT expression in women with invasive breast ductal carcinoma who underwent mastectomy/lumpectomy without neo-adjuvant treatment. We showed that MT was over-expressed in 87.9% of breast cancer tissues examined, with the mean percentage of positive cells at 30%. There were two patterns of MT expression: predominantly cytoplasmic in 75.9% and nuclear in 24.1% of MT-positive cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 32 publications
5
50
0
4
Order By: Relevance
“…Jin et al found that in breast cancer cases of the highest malignancy G3, expression of MT was significantly higher than in better differentiated cases, G1 and G2 [41,44]. Similar observations were made recently by Yap et al [36]. In turn, Gallicchio et al in the studied group of 110 cases of ductal breast cancer demonstrated a strong positive correlation between intensity of MT expression and grade of malignancy [45].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Jin et al found that in breast cancer cases of the highest malignancy G3, expression of MT was significantly higher than in better differentiated cases, G1 and G2 [41,44]. Similar observations were made recently by Yap et al [36]. In turn, Gallicchio et al in the studied group of 110 cases of ductal breast cancer demonstrated a strong positive correlation between intensity of MT expression and grade of malignancy [45].…”
Section: Discussionsupporting
confidence: 66%
“…Several authors showed an evident relationship between intensity of MT expression and clinical advancement of the tumours, frequency of metastasis development, as well as shortening of survival rate and disease free survival [17,28,[31][32][33][34]. In some tumours also a significant correlation between high levels of MT and unfavourable results of treatment was observed [30,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Although metatypic BCC is regarded as an aggressive subtype of BCC, it manifested the lowest MT-I/II expression of the analyzed subtypes. We used IHC techniques to determine MT-I/II expression, but recent studies have shown that only particular MT-I/II isoforms may contribute to cancer cell aggressiveness in some tumor types [31][32][33][34][35]. In our study, we noted the highest Ki-67 antigen expression in this subtype.…”
Section: Discussionsupporting
confidence: 47%
“…Several studies have reported MT expression in various human malignancies including STSs and BSs [6][7][8][9], and there is evidence that MT plays a role in cancer development [10], prognosis [6], and treatment resistance [11]. With respect to cancer therapy, MT can protect against radiation therapy [12] and anticancer drugs [10,13], most likely due to their anti-oxidant properties. Remarkably, MT can counteract the effect of melphalan [14,15], the active cytotoxic component of HILP-TM treatment.…”
Section: Introductionmentioning
confidence: 99%